A - Fikayuniar, Lia; Yuniarsih, Nia; Abriyani, Ermi; Ayesha, Adinda (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Temulawak (Curcuma xanthorrhiza Roxb) is a rhizome plant that has long been used in traditional medicine in Indonesia. The active compounds in temulawak function as antioxidants, which are essential in combating free radicals and preventing cell damage. This study aims to compare the antioxidant activity of ethanol extracts of temulawak obtained through maceration and ultrasonic extraction methods. The research method applied is pre-experimental, with testing conducted in triplicate to ensure result validity. Antioxidant activity was evaluated using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The results show that the ethanol extract of temulawak obtained via maceration method has an IC50 value of 33.379 µg/ml. In contrast, the ultrasonic extraction method showed a lower IC50 value of 9.454 µg/ml, indicating stronger antioxidant activity. Temulawak, as an antioxidant source, has significant potential in the development of herbal products. The comparison of the two extraction methods shows that the ultrasonic method is more effective in enhancing antioxidant activity. This study emphasizes that the extraction method influences the antioxidant activity of temulawak. These results could serve as an important reference for the development of herbal-based products in the future.